Performance of Real-Time Semi-Quantitative Polymerase Chain Reaction Assay for Optimum Diagnosis of Extrapulmonary Tuberculosis and Sensitivity to Rifampin in a Tertiary Care Center - Adrián Peñata-Bedoya; Shally Zuluaga-Avendaño; Tatiana Castaño-Sepúlveda; Julián Bustamante-Mira; Sigifredo Ospina-Ospina (Permanyer, 2021)
Background: Tuberculosis represents a public health problem, with extrapulmonary disease occurring in 15% of incident cases annually. Early diagnosis is a challenge due to its paucibacillary nature. Recently, a molecular real-time semi-quantitative assay (GeneXpert Ultra) was developed to overcome limitations of the previous assay version (Xpert MTB/RF). Objective: The objective of the study was to assess the usefulness of the novel next-generation GeneXpert assay in extrapulmonary samples from different anatomic sites under routine diagnostic conditions at a university medical center. Methods: A total of 519 samples from patients with presumptive diagnosis of extrapulmonary TB were subjected to smear microscopy, culture, and molecular assay. Univariate analyses for demographic and microbiological characteristics were performed. The sensitivity, specificity, and Kappa index with a 95% confidence interval were determined. Results: Molecular assay was positive in 53 samples (10.2%), of which 38 (71.6%) belonged to the "low" and "trace" semi-quantitative categories. The overall sensitivity and specificity were 86.4% (95% confidence intervals [CI]: 74.1-98.8) and 95.6% (95% CI: 93.7-97.6), respectively. Phenotypic drug susceptibility testing for rifampin was 100% concordant. Conclusions: Molecular assay showed significant results when compared to other standard tests, making it a useful tool that could lead in the improvement to a rapid diagnosis of extrapulmonary disease.